Development of single cylinder engine test rig for small engine dyno - Nazirul Izzat, Ibrahim (2010)
This work is on the design and fabrication of a test rig structure that suite to the engine MODENAS Kriss 110cc. The objective of the report is to design and fabricate a test rig structure that suite to the engine MODENAS Kriss 110cc. This project also describes the review of products which are available around the world following to the title of the project. Design generation is showed and solid three dimensional structures modelling of the test rig structure that suite to the engine MODENAS Kriss 110cc was developed with computer aided design software. This report also explain the fabrication process that be needed for this project. Descriptions of material also show on this report. The problems encountered during completion of this project are also show in the report. An Improvement of the test rig structures that suite to the engine MODENAS Kriss 110cc needs for further application.